Analysis of Irradiation on the Clinical Effectiveness of Allogenic Tissue When Used for Primary Anterior Cruciate Ligament Reconstruction. (January 2015) - Park, Sam Si-Hyeong; Dwyer, Tim; Congiusta, Francesco; Whelan, Daniel B.; Theodoropoulos, John
Background: It is unclear whether the use of low-dose irradiation or other tissue-processing methods, such as preservation by fresh-frozen (FF), freeze-drying (FD), or cryopreservation (CP) methods, affects the clinical outcomes of primary anterior cruciate ligament reconstruction (ACLR) using allograft. Hypothesis: Low-dose gamma irradiation (<2.5 Mrad) and method of allograft preservation do not affect subjective and objective clinical outcomes after primary ACLR in studies reviewed between November 2010 and September 2012. Study Design: Systematic review; Level of evidence, 3. Methods: A computerized search of multiple electronic databases was conducted from November 2010 to September 2012 for prospective and retrospective studies involving primary allograft ACLR. Inclusion criteria were English-language publications with a minimum average of 2 years' follow-up. Studies were excluded if they involved revision surgery, open surgery, multiple ligament procedures, autograft, xenograft, meniscal allograft, skeletally immature patients, or grafts treated with ethylene oxide, Tutoplast, or irradiation >2.5 Mrad or if the tissue-processing methods were not specified. Clinical outcomes were evaluated using the Lysholm score, Tegner score, International Knee Documentation Committee (IKDC) score, KT-1000/2000 arthrometer score, Lachman test, and pivot-shift test, as well as by assessing complications related to graft rupture, revision surgery, and infections. Results: A total of 21 publications met the criteria, involving a total of 1453 patients, with 415 irradiated and 1038 nonirradiated allografts. Mean follow-up was 49.8 months (range, 12-170 months). Mean age of the patients was 32.2 years. Knees with nonirradiated allografts had higher mean Lysholm scores (89.8 vs 84.4; P < .05), and a higher proportion of <5-mm difference on KT-1000/2000 arthrometer (0.97 vs 0.84; P < .0001), grade 0 and 1 pivot-shift (0.99 vs 0.94; P < .0001), and grade 0 and 1 Lachman (0.94 vs 0.89; P < .01) than those with irradiated grafts. Knees with irradiated allografts had a higher proportion of grade A and B IKDC outcomes (0.91 vs 0.86; P < .05) and revision surgery (0.0250 vs 0.0022; P < .001) compared with those with nonirradiated allografts. The lack of data for FD and CP allografts meant no statistical analysis could be made comparing FF versus FD versus CP allografts. The effect of irradiation was similar within FF allografts. The effect of graft type and surgical technique could not be determined because of insufficient data. Conclusion: These results suggest that primary ACLRs using nonirradiated allografts may provide superior clinical outcomes than those using low-dose (<2.5 Mrad) irradiated grafts.